If not for you : a novel - Macomber, Debbie (Macomber, Debbie. New beginnings series., 2017)
"Having lived under her parents' thumb for 25 years, Beth Prudhomme is finally taking charge of her own life. She moves from Chicago to Portland to live near her favorite aunt, finding employment as a music teacher at a local high school and a fast friend in Nichole Nyquist (who readers will recognize from A Girl's Guide to Moving On). Everything is coming together, though her love life leaves something to be desired. Until Nichole introduces Beth to Sam, a tattooed mechanic who's the epitome of her conservative parents' worst nightmare. Beth doesn't want to upset her parents more than she already has, and for himself, Sam has no interest in being set up with a prissy music teacher. But both learn that appearances aren't everything when Beth gets into a car accident and Sam visits her--at first out of obligation, and then because he can't stay away. Yet there are skeletons in Sam's closet that prevent him from ever trusting a woman again, and he knows he doesn't fit into Beth's life. In the end, he'll have to decide if he can ever be worthy of Beth's love and if he is, how far he's willing to go to fight for it"--